“THE ROLE OF CULINARY FESTIVALS AND EVENTS IN PROMOTING GASTRONOMIC TOURISM IN UZBEKISTAN” (Journal of Uzbekistan’s Development and Research, 2025)
This article examines the role of culinary festivals and events in promoting gastronomic tourism in Uzbekistan, with a focus on leveraging the country's rich culinary heritage to attract tourists. It explores Uzbekistan's diverse and historically significant cuisine, the current state of gastronomic tourism, and emerging opportunities for development.